Can serumpun still binds Malays and Indonesians after recent cultural flare-ups? - Rusli, Mohd Hazmi; Mustafa, Maizatun (2014)
It has been more than a year since the last cultural ‘flare-ups’ took place between Malaysia and Indonesia. Undeniably, the concept of serumpun has always been a major factor underlying the relationship between Malaysia and Indonesia. How far has the concept of serumpun influenced the solidarity of both Malaysians and Indonesians today? Commentary THE word rumpun or serumpun, meaning‘of the same root’ in Malay/Indonesian, is a concept that is principally embraced by both Malaysians and Indonesians, particularly the Malays. History has recorded that the area of what it is now Malaysia and Indonesia was for centuries under the dominions of powerful kingdoms of the Malay race namely Srivijaya, Majapahit, the Malacca Sultanate and other sultanates like Johor, Aceh, Brunei and Gowa. It was not until the advent of colonialism and eventually the Anglo-Dutch Treaty of 1824 that the Malay Archipelago was separated into two spheres of colonial dominions. ....